Implementation of Simplified Financial Statements in Micro And Small Enterprises in Poland - Adrianna LISOWSKA (Communications of International Proceedings, 2021)
The simplifications introduced in 2014 and 2015 in the templates of financial statements for micro and small business entities aimed to reduce the administrative costs incurred by these enterprises. The article aims to identify the degree of implementation of simplifications in the financial statements of micro and small enterprises, consistent with Polish regulations - the Accounting Act. In the theoretical part of the study - based on literature studies - micro and small enterprises are characterized, and the scope of simplifications used in financial statements for these entities is presented. The empirical part indicates the everyday use of simplifications in the financial statements of micro and small enterprises in 2018, based on own research. Five hundred financial statements of limited liability companies from the Lodz Voivodship were examined, which, following the Act of 29 September 1994 on accounting (Journal of Laws 1994, No. 121 items 591), met the conditions of a micro or small entity. The document examination method was used for the study.
Keywords: Microenterprises; Small enterprises; Financial statements.